ISOLATION AND CHARACTERIZATION OF CHITIN AND CHITOSAN PREPARED UNDER VARIOUS PROCESSING TIMES - Crescentiana Dewi Poeloengasih; Hernawan Hernawan; M. Angwar (Universitas Gadjah Mada, 2008)
Generally production of chitosan from crustacean shells consists of 4 steps, i.e. deproteinization, demineralization, decolorization and deacetylation. Simplification of chitosan production by elimination of deproteinization and/or demineralization, or reducing of reaction time would give many advantages, e.g. reduction of processing time and cost production due to reduction of chemical and power usage. The objectives of this research were to prepare chitosan under various processing times and to characterize the obtained chitin and chitosan. Chitin was prepared under various deproteinization times (0, 15, 30 min at 90 ºC using NaOH 2N) and demineralization times (0, 15, 30 min at ambient temperature using HCl 2N). Chitin was then bleached using aceton/etanol (1:1) for an hour. Deacetylation was achieved by treatment of chitin under condition at 120 ºC for 5 hr using NaOH 50%. Ash and nitrogen content, and degree of deacetylation of chitosan were evaluated. Demineralization and/or deproteinization times influenced the quality of chitin. Chitin and chitosan prepared without demineralization had white and chalky appearance, whereas the other chitosan were off-white in color. Ash and nitrogen contents of the chitosan products were 0.18 - 32.40% and 3.56 - 7.59%, respectively. Chitosan prepared under various processing times, except chitosan without demineralization treatment, had degree of deacetylation ≥ 70%.